Analisis Wacana Kritis Norman Fairclough pada Video YouTube Zulfan Lindan "Unpacking Indonesia" - Nisa Halisa Hakim (PRASASTI: Journal of Linguistics, 2025)
This study aims to analyze critical discourse in the podcast on the YouTube channel Zulfan Lindan Unpacking Indonesia entitled "DPR dan Menteri Nadiem Cuek atas Kurikulum Membodohkan Siswa!: AHMAD BAIDHOWI (AHLI PENDIDIKAN)" through Norman Fairclough's critical discourse analysis approach. The podcasts discusses Indonesia's national education management system during Nadiem Makariem's leadership, highlighting frequent changes in the education curriculum and increasing UKT in universities. This study uses Norman Fairclough's critical discourse analysis model, which includes three dimensions: text analysis, discourse practice, and social practice. The analysis results show that the discussion revealed various problems in education governance in Indonesia, such as a non-transparent budget, frequent curriculum changes without evaluation, and UKT increases that burden students. In addition, the results of this study show that Ahmad Baidhowi's speech in the podcast video taken from the YouTube channel Zulfan Lindan Unpacking Indonesia entitled "DPR dan Menteri Nadiem Cuek atas Kurikulum Membodohkan Siswa!: AHMAD BAIDHOWI (AHLI PENDIDIKAN)" effectively presented various types of discourse analysis developed by Norman Fairclough in 1995, including Text Analysis, Discourse Practice, and Social Practice. This analysis identified 24 data with 22 dimensions of text analysis, 1 dimensions of discourse practice, and 1 dimensions of social practice.